2023
DOI: 10.1111/cobi.14092
|View full text |Cite
|
Sign up to set email alerts
|

Obstruction of biodiversity conservation by minimum patch size criteria

Abstract: Minimum patch size criteria for habitat protection reflect the conservation principle that a single large (SL) patch of habitat has higher biodiversity than several small (SS) patches of the same total area (SL > SS). Nonetheless, this principle is often incorrect, and biodiversity conservation requires placing more emphasis on protection of large numbers of small patches (SS > SL). We used a global database reporting the abundances of species across hundreds of patches to assess the SL > SS principle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Our results challenge the idea that fragmentation per se has largely negative effects on species persistence. Indeed, the positive response of the ÅGFB to fragmentation per se adds to other work suggesting that small patches often have disproportionately high conservation value relative to their areas (Riva & Fahrig, 2022; Wintle et al., 2019), including very small patches (Arroyo‐Rodríguez et al., 2022; Riva & Fahrig, 2023b). We found this same result for a species that is thought to epitomize sensitivity to habitat fragmentation, which indicates that a paradigm shift in conservation is needed.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Our results challenge the idea that fragmentation per se has largely negative effects on species persistence. Indeed, the positive response of the ÅGFB to fragmentation per se adds to other work suggesting that small patches often have disproportionately high conservation value relative to their areas (Riva & Fahrig, 2022; Wintle et al., 2019), including very small patches (Arroyo‐Rodríguez et al., 2022; Riva & Fahrig, 2023b). We found this same result for a species that is thought to epitomize sensitivity to habitat fragmentation, which indicates that a paradigm shift in conservation is needed.…”
Section: Discussionmentioning
confidence: 67%
“…We found this same result for a species that is thought to epitomize sensitivity to habitat fragmentation, which indicates that a paradigm shift in conservation is needed. In particular, we see the need for a shift away from policies that place lower limits on the sizes of conserved areas (Riva & Fahrig, 2023b) or that emphasize “defragmenting” landscapes. Past and current lack of protection for small patches of habitat has real consequences.…”
Section: Discussionmentioning
confidence: 99%
“…From a theoretical perspective, the framework builds on metapopulation theory, including more flexible assumptions and broadening its applicability. By integrating the effects of both habitat degradation and loss of connectivity or fragmentation into a quantitative metric (Rubio & Saura, 2012), the habitat functionality framework goes beyond simplistic dichotomies that might hinder conservation practice (whether to manage single large or several small habitat patches; Riva & Fahrig, 2023; Szangolies et al, 2022) and has great potential to guide sustainable land planning. This makes the framework ideally suitable for assessing the cumulative impacts of anthropogenic activities, including infrastructure development, land‐use changes and climatic changes (Dorber et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, empirical studies have always suggested that HF has negative direct and indirect effects on biodiversity [50,51]; however, more recently, these theories have been the subject of renewed discussion [4] since a multitude of studies have yielded contrasting…”
Section: Discussionmentioning
confidence: 99%
“…Its community-shaping action has been demonstrated across all ecosystems, from terrestrial to aquatic ones [2]. HF is at the core of a long debate that started with MacArthur and Wilson's [3] theory of island biogeography and that extended over the successive six decades up to the recent work by Riva and Fahrig [4]. Riva and Fahrig hypothesised that the ecological role played by patchiness, although raising a number of questions, is addressed within a considerable body of literature confirming that the assessment of HF is a complex exercise [5].…”
Section: Introductionmentioning
confidence: 99%